Validity and reliability of isometric tests for the evidence-based assessment of arm strength impairment in wheelchair rugby classification - Mason, B. S.; Altmann, V. C.; Hutchinson, M. J.; Goosey-Tolfrey, V. L. (Journal of Science and Medicine in Sport, 2020)
Objectives: The purpose of this study was to examine the validity and test-retest reliability of a battery of single-joint isometric strength tests, to establish whether the tests could be used for evidence-based classification in wheelchair rugby (WR). Design: Cross-sectional. Methods: Twenty male WR athletes with impaired arm strength and thirty able-bodied (AB) participants (15 male, 15 female) performed four isometric strength tests. Each test required three 5-s efforts and examined maximal isometric force for flexion and extension around the shoulder and elbow joint. Test validity was established by comparing differences (Cohen`s effect sizes [d]) in strength between WR athletes and AB participants. Differences were also explored between male and female AB participants. Twenty AB participants returned for a second visit to establish the test-retest reliability of the test battery. Results: Significantly lower force values were observed for all isometric strength measures in WR athletes compared to AB participants (p = 0.0005; d = 2.14). Female AB participants also produced significantly less force than male AB participants for all joint actions (p = 0.0005; d = 1.93). No significant differences were identified between trials for any measure of strength, with acceptable levels of test-retest reliability reported (ICCs = 0.97, SEM = 19.3 N and CV = 8.4%). Conclusions: The current results demonstrated the validity of a battery of isometric strength tests, suggesting they can be used to reliably infer strength impairment in WR athletes, which is a pre-requisite when working towards evidence-based classification in Paralympic sport.